A qualitative and quantitative investigation of effects of indoor built environment for people with dementia in care and attention homes. (15th June 2019) - Leung, Mei-yung; Wang, Chendi; Chan, Isabelle Y.S.
Abstract: The demented elderly have physical, emotional and behavioral patterns that differ from those of the normal elderly, and those patterns differentiate their needs in terms of the indoor built environment (IBE). Therefore, it is essential to investigate the effects of the IBE on the quality of life (QoL) of the demented elderly. To ensure the study's reliability and validity, multiple research methods were applied, including qualitative methods (i.e., an interview) and quantitative ones (i.e., a questionnaire survey). In total, 96 demented elderly residents and 18 caregivers from eight care and attention (C&A) homes were involved in the current study. Based on the data collection, an IBE-QoL model was developed using a reliability test, correlation analysis and regression analysis. The model confirmed the following: 1) building services factors – lighting, temperature, lifts and water supply – predict demented elderly residents' physical health, psychological health, independence, activities of daily living and social relationships; and 2) supporting facilities factors – signage, finishes and furniture – also exert a positive impact on the residents' physical health, activities of daily living, social relationships and cognitive functioning. Practical recommendations are made, including that C&A homes provide access to a sky garden on each floor, label water taps with hot/cold signs, provide signage with iconic information at different strategic locations, employ color contrasting finishes in different rooms, use historical furniture, and so on. This study's results provide valuable insight into improving C&A homes' IBE in order to enhance the QoL of the demented elderly. Highlights: Six QoL domains and twelve indoor built environment (IBE) factors are identified. The existing IBE in care and attention homes are generally unsatisfactory. An IBE-QoL model for the demented elderly is built using multiple research methods. Four building services factors positively predict their QoL of the demented elderly. Three supporting facilities positively affect their QoL and cognitive functioning.